IDEA OF THE WORLD OF TURKIC PEOPLES OF CENTRAL ASIA: ANTIQUITY AND EARLY MIDDLE AGES - Molotova Г.М. (Journal of Oriental Studies, 2024)
The article uses data from Ancient Turkic written monuments published in the Soviet period. The author intends to illuminate the idea of the world of Turkic peoples of Central Asia. The main sources were the inscriptions on the stone “Monument in honor of Kul-Tegin”, “Monument in honor of Tonyukuk” and “Irq-bitig”, which were preserved on paper. The author of the article notes that, despite the knowledge of stone steles, some facets of these sources remain poorly studied. The idea of a three-level horizontal and quadrangular vertical model of the world is being considered. It is noted that such a view is common to the Turkic peoples of Central Asia and Southern Siberia. Directly with this question, the supporting and punishing function of representatives of the ancient Turkic pantheon of deities is covered. By comparative analysis of monuments in honor of Kul-Tegin, Tonyukuk with data from epigraphy of the same period, additional data about the function of the goddess Umai was established. The transformation of the Umai function was established based on data recorded in the “Divan Lughat at-Turk” by Mahmud Qashghari. The archaic myth about the creation of the Universe has been determined. The conclusion notes the importance of ancient Turkic written monuments for studying the spiritual values of the Turkic peoples of Antiquity and the Early Middle Ages. Keywords: ancient Turkic written monuments, the idea of the world, the model of the world, Qaghan, Central Asia.